Propose a MPPT Algorithm Based on Thevenin Equivalent Circuit for Improving Photovoltaic System Operation - Nguyen, Binh Nam; Nguyen, Van Tan; Duong, Minh Quan; Le, Kim Hung; Nguyen, Huu Hieu; Doan, Anh Tuan (Frontiers in Energy Research, 2020)
Various maximum power point tracking methods (MPPT) for photovoltaic (PV) power systems have been considered and developed to maximize the delivered possible power. The output power of PV cells with nonlinear characteristics is affected by temperature, solar irradiation and load. In this paper, a modelized photovoltaic source is proposed, based on the Thevenin equivalent circuit at the beginning. A ordinarily employed solar system model is linearized into simple Thevenin source-resistance representation. Next, a control algorithm associated with the relationship between controller’s PWM duty cycle of the MPPT boost converter and solar array output power, namely proposed MPPT algorithm, is introduced. This proposed method is compared with an existing popular MPPT algorithm to confirm its superior performance by using the MATLAB/SIMULINK simulation. Finally, a 50W DC-DC boost converter prototype is implemented and tested to verify the feasibility of the proposed control scheme.